Avaliação da durabilidade de concretos com incorporações de pó de pedra e resíduo de construção e demolição (RCD) - Dantas, Samuel Queiroz (Universidade Federal Rural do Semi-Árido, 2019)
Given the current scenario, where the scarcity of natural material deposits has become a concern, the construction industry is seen as one of its major consumers, and is also responsible for generating a large amount of solid waste due to its construction and demolition activities. Thus, in recent years the possibility of incorporating waste in the production of mortars, concrete, paving, among other products has been studied. This work aimed to study the influence on the durability of concrete with the incorporation of stone dust, resulting from the crushing process and the construction and demolition waste (RCD). The material characterization tests were carried out, which proved to be similar to the partially replaced natural aggregates, sand, with 10% stone dust and gravel, in the proportions of 5%, 10% and 15%. of substitution. For the concrete, the tests were carried out for the reduction of the cone trunk and specific mass for the fresh state, which showed that despite a reduction in the first one, the concrete maintains its workability, thus being able to be applied in this way or to try to improve this. property with the use of additives. In the hardened state was verified the penetration of chloride and absorption, the results showed that, under condition of pre-saturation of the RCD, there was an improvement in the durability of concrete, since there is a reduction in the penetration of chloride ions, also realizing that in Lower amounts of incorporation achieve better results, with the trait including both 10% stone dust and 5% RCD the most suitable for the reuse of these residues.
Keywords: Cloretos; Cimento Portland; Nitrato de prata; Durabilidade; Chloride; Portland cement; Silver nitrate; Durability; ENGENHARIAS::ENGENHARIA CIVIL